A political sociology of education policy - Gunter, Helen (Policy Press, an imprint of Bristol University Press, 2023)
This book aims to restore the role of political analysis in education policy by presenting a new political sociology for framing, conducting and presenting research. In doing so, it will be the first in the field to connect political thinking from Arendt with sociological thinking from Bourdieu.